Penerapan Steganografi untuk Menyembunyikan Teks dan File dalam Gambar PNG dan BMP sebagai Perlindungan Informasi - Darel, Aldo; Artha Sitorus; Laura Pasaribu (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2026)
Information security is an urgent need in today's digital era, especially to protect confidential data from unauthorized access. This research proposes the application of steganography using the Least Significant Bit (LSB) method to hide text and files in PNG and BMP format images. This steganography technique aims to disguise the presence of confidential information, making it difficult to detect by third parties. The LSB method allows the insertion of information without significantly reducing the visual quality of the image. The developed application allows users to insert a secret message into an image and extract the information easily. Test results show that the application is effective in maintaining data confidentiality and integrity, and can save various file formats such as .txt, .docx, and .pdf. It is hoped that, by using this method, increasingly complex information security challenges can be overcome and provide additional protection to the copyright of digital products.